Analisis Strategi Pengembangan Kota Pintar (Smart City) di Kota Bandung - Sri Wahyuni; Lucky Satria Pratama; Cindy Indah Yani; Prety Sapahira; Kartika Kartika; Muhammad Faiz; Roffi Rivaldo Arya Suta; Wahyu Habib Wardhana (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This phenomenon occurs such as congestion, cleanliness, lack of transportation services, and lack of service are the causes of problems. This study aims to determine the Smart City Development Strategy (Smart City) in the city of Bandung. This study uses a quantitative approach in the form of numbers. The type of data used is using primary data in the form of a questionnaire. Research using the number of respondents as many as 97 people. Statistical tests and data processing were carried out using Partial Least Square (SmartPLS 4). The research findings show that: (1) Smart Branding has no effect on the development strategy; (2) Smart Economy has no effect on the Development Strategy; (3) Smart Living has no effect on the Development Strategy; (4) Smart Society influences Development Strategy; (5) Smart Environment influences Development Strategy; (6) Smart Governance has no effect on the Development Strategy; (7) Smart Branding has no effect on the Development Strategy through Smart Governance; (8) Smart Economy has no effect on the Development Strategy through Smart Governance; (9) Smart Living has no effect on the Development Strategy through Smart Governance; (10) Smart Society has no effect on the Development Strategy through Smart Governance; (11) Smart Environment has no effect on Development Strategy through Smart Governance. With an improved Smart Society and Smart Environment, the Development Strategy in the City of Bandung will also be easy to realize which aims for the growth of the City of Bandung.